Complex Immune Contextures Characterise Malignant Peritoneal Mesothelioma: Loss of Adaptive Immunological Signature in the More Aggressive Histological Types. (29th October 2018) - Tazzari, Marcella; Brich, Silvia; Tuccitto, Alessandra; Bozzi, Fabio; Beretta, Valeria; Spagnuolo, Rosalin D.; Negri, Tiziana; Stacchiotti, Silvia; Deraco, Marcello; Baratti, Dario; Camisaschi, Chiara; Villa, Antonello; et al.
Abstract : Malignant peritoneal mesothelioma (MpM), arising in the setting of local inflammation, is a rare aggressive tumour with a poor prognosis and limited therapeutic options. The three major MpM histological variants, epithelioid (E-MpMs), biphasic, and sarcomatoid MpMs (S-MpMs), are characterised by an increased aggressiveness and enhanced levels of EZH2 expression. To investigate the MpM immune contexture along the spectrum of MpM histotypes, an extended in situ analysis was performed on a series of 14 cases. Tumour-infiltrating immune cells and their functionality were assessed by immunohistochemistry, immunofluorescence, qRT-PCR, and flow cytometry analysis. MpMs are featured by a complex immune landscape modulated along the spectrum of MpM variants. Tumour-infiltrating T cells and evidence for pre-existing antitumour immunity are mainly confined to E-MpMs. However, Th1-related immunological features are progressively impaired in the more aggressive forms of E-MpMs and completely lost in S-MpM. Concomitantly, E-MpMs show also signs of active immune suppression, such as the occurrence of Tregs and Bregs and the expression of the immune checkpoint inhibitory molecules PD1 and PDL1. This study enriches the rising rationale for immunotherapy in MpM and points to the E-MpMs as the most immune-sensitive MpM histotypes, but it also suggests that synergistic interventions aimed at modifying the tumour microenvironment (TME) should be considered to make immunotherapy beneficial for these patients.